Can repair increase the longevity of composite resins? Results of a 10-year clinical trial - Fernández, Eduarddo [UNESP]; Martin, Javier [UNESP]; Vildósola, Patricio [UNESP]; Oliveira Júnior, Osmir Batista de [UNESP]; Gordan, Valéria; Mjor, I.; Bersezio, Cristian [UNESP]; Estay, Juan [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Moncada, Gustavo [UNESP] (Elsevier, 2015)
The aim of this double-blind clinical trial was to assess the longevity of repairs to localized clinical defects in composite resin restorations that were initially planned to be treated with a restoration replacement. Methods Twenty-eight patients aged 18–80 years old with 50 composite resin restorations (CR) were recruited. The restorations with localized, marginal, anatomical deficiencies and/or secondary caries adjacent to CR that were “clinically judged” to be suitable for repair or replacement according to the USPHS criteria were randomly assigned to Repair (n = 25) or Replacement (n = 25) groups, and the quality of the restorations was scored according to the modified USPHS criteria. The restorations were blind and two examiners scored them at baseline (Cohen Kappa agreement score 0.74) and at ten years (Cohen Kappa agreement score 0.87) restorations. Wilcoxon tests were performed for comparisons within the same group (95% CI), and Friedman tests were utilized for multiple comparisons between the different years within each group. Results Over the decade, the two groups behaved similarly on the parameters of marginal adaptation (MA) (p > 0.05), secondary caries (SC) (p > 0.05), anatomy (A) (p < 0.05), and colour (C) (p > 0.05). Conclusions Given that the MA, SC, A and C parameters behaved similarly in both groups, the repair of composite resins should be elected when clinically indicated, because it is a minimally invasive treatment that can consistently increase the longevity of restorations. Clinical significance The repair of defective composite resins as an alternative treatment to increase their longevity proved to be a safe and effective treatment in the long term.
Keywords: Composite resins; Restoration; Repair; Replacement; Clinical trial